Antibiotic Resistance of Pathogens of Generalized Purulent Septic Infections in Children - O. A. Noskova; E. D. Savilov; N. N. Chemezova; N. L. Belkova (Эпидемиология и вакцинопрофилактика)
Relevance. Microbiological monitoring in medical organizations is an essential part of ensuring epidemiological safety in the provision of medical care. The study of the sensitivity of pathogens to antibacterial drugs allows us to reasonably approach the prescription of empirical therapy and form a form of antibacterial agents for medical organization. The purpose of the work was to study the species composition of pathogens of generalized purulent septic infections (GPSI) in a children's multidisciplinary hospital and determine their resistance to antibacterial drugs. Materials and methods. Analysis of microbiological analysis data of material taken from patients with GPSI treated in children's multidisciplinary hospital in the period 2013-2018 was carried out. A total of 572 cultures were studied. Results. It was found that the largest specific gravity in the structure of GPSI was occupied by gram-negative microorganisms, the proportion of which significantly decreased from 73.0% in 2013 to 48.1% in 2018. Gram-positive microorganisms were found in 27.0 ± 8.1% cases, while a significant increase in the proportion of fungi from 5.4 to 30.7% was observed. The antibiotic resistance of the main pathogens has been studied. Among non-fermenting gram-negative bacteria, the highest (p < 0.05) multi-resistivity indicator was found in Acinetobacter baumannii (50.0 ± 6.8%). Enterococcus, having high natural resistance to a number of antibiotic groups, leave the possibility of effective action of the preparation of the group of glycopeptides (vancomycin) against Enterococcus faecium. Conclusions. High pathogens to applied antibacterial preparations is shown. The obtained data make it possible to form an up-to-date form of antimicrobial drugs for use in children's hospitals, to develop measures that inhibit the development of resistance in pathogens of purulent-inflammatory diseases.